The biasing effect of evocative attributes at the implicit and explicit level: The tradition halo and the industrial horn in food products evaluations. (July 2021) - Richetin, Juliette; Demartini, Eugenio; Gaviglio, Anna; Ricci, Elena Claire; Stranieri, Stefanella; Banterle, Alessandro; Perugini, Marco
Abstract: This contribution investigates the role of food product attributes on consumer choices focusing on different production processes, labeled as 'traditional' or 'industrial'. More specifically, we aim at documenting a novel halo (positive) effect of the Tradition label versus a horn (negative) effect of the Industrial label on the implicit and explicit perceptions of healthiness and tastiness of a food product using an experimental design as well as potential moderation effects of pro-environmental beliefs. In four studies, we manipulated the label of two brands of cheese regarding their production process (Study 1 and Study 2: traditional vs. industrial, Study 3: traditional vs. no label, Study 4: industrial vs. no label) and we measured implicit (with SC-IAT in Study 1, SA-IAT in Study 2, and IAT in Study 3 & 4) and explicit (self-report) perceptions of healthiness and tastiness. Results showed a Tradition halo effect and an Industrial horn effect on explicit perceptions of tastiness and healthiness. Results on implicit perceptions of healthiness seem to depend to some extent on pro-environmental beliefs. Results suggest that tradition-labeled food should be introduced in conventional supermarkets instead of investing in the opening of new specialized stores.